Global Report on Trafficking in Persons 2009 - United Nations Office on Drugs; Crime (United Nations, 2009)
The Global Report on Trafficking in Persons provides new information on a crime that shames us all. Based on data gathered from 155 countries, it offers the first global assessment of the scope of human trafficking and what is being done to fight it. It includes: an overview of trafficking patterns; legal steps taken in response; and country-specific information on reported cases of trafficking in persons, victims, and prosecutions. The most common form of human trafficking (79%) is sexual exploitation. The victims of sexual exploitation are predominantly women and girls. Surprisingly, in 30% of the countries which provided information on the gender of traffickers, women make up the largest proportion of traffickers. In some parts of the world, women trafficking women is the norm. The second most common form of human trafficking is forced labour (18%), although this may be a misrepresentation because forced labour is less frequently detected and reported than trafficking for sexual exploitation. Worldwide, almost 20% of all trafficking victims are children. However, in some parts of Africa and the Mekong region, children are the majority (up to 100% in parts of West Africa). Although trafficking seems to imply people moving across continents, most exploitation takes place close to home. Data show intra-regional and domestic trafficking are the major forms of trafficking in persons.